Recurrent Hepatitis E in Pregnancy - Rehana Yasmeen'; Rubina Hussain; Anjum Afshan (ziauddin University, 2024)
ABSTRACT Hepatitis E virus (HEV) is a single stranded RNA virus that causes large scale epidemics of acute viral hepatitis, particularly in developing couniries. In men and non pregnant women, the disease is usually self limited and has a case fatality rate of less than < 0.1%. However in pregnant women HEVinfection is more severe often leading to fulminant hepatic failure and death in a significant proportion of patients. The high mortality rate in pregnancy has been thought to be secondaryto the associated hormonal changes during pregnancy and consequent immunological changes. Recurrent hepatitis E in pregnancy is a severe and rare condition. We report an interesting case of recurrent hepatitis E in pregnancy. Key Words: Recurrent Hepatitis E Virus Infection, Pregnancy.